Effectiveness of Evaluation Used in Online Education at Primary Level: Parent’s Perception - Bhattacharya, Trisha; Shukla, Rekha (THE PRIMARY TEACHER, 2022)
“Children are not things to be molded, but are people to be unfolded ...” and their learning in their initial years is a milestone for their future. COVID-19 has suddenly shifted the classroom to their home from school. This had a great impact on the teaching learning and evaluation process of students, especially at the primary level as they are less adaptive to sudden change. The small students usually have a play way and activity based learning. This study is on the perception of parents on the effectiveness of the evaluation process used in online education for the primary level. It is very important at this stage of education that a proper evaluation methodology should develop for these little ones as this pandemic has taught us to be future-ready in all the fields including education. This study help find the parent’s perception on the evaluation process of virtual classes and will lead us to certain conclusions and suggestions regarding the evaluation process.